9) 2х-5=7(3х+4)+5
2х-5=21х+28+5
2х-21х=28+5+5
-19х=38
х=38:(-19)
х=-2
10) 28-4(3х+2)=5(2х-7)
28-12х-8=10х-35
12х-10х=-35-28+8
-2х=1
х=-0,5
11) 3х-4(5х+2)-6(3х-4)=1
3х-20х-8-18х+24=1
3х-20х-18х=1+8-24
0х=-15
нет корней
12) 7(х-4)+3=-5(2х-7)+х-8
7х-28+3=-10х+35+х-8
7х+10х-х=35-8+28-3
16х=52
х=52:16
х=31/4
9) 2х-5=7(3х+4)+5
2х-5=21х+28+5
2х-21х=28+5+5
-19х=38
х=38:(-19)
х=-2
10) 28-4(3х+2)=5(2х-7)
28-12х-8=10х-35
12х-10х=-35-28+8
-2х=1
х=-0,5
11) 3х-4(5х+2)-6(3х-4)=1
3х-20х-8-18х+24=1
3х-20х-18х=1+8-24
0х=-15
нет корней
12) 7(х-4)+3=-5(2х-7)+х-8
7х-28+3=-10х+35+х-8
7х+10х-х=35-8+28-3
16х=52
х=52:16
х=31/4